2018
DOI: 10.1136/bjsports-2017-098696
|View full text |Cite
|
Sign up to set email alerts
|

Femoroacetabular impingement surgery allows 74% of athletes to return to the same competitive level of sports participation but their level of performance remains unreported: a systematic review with meta-analysis

Abstract: CRD42017072762.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 57 publications
3
61
1
1
Order By: Relevance
“…Hence, in light of our findings, previously reported RTS rates of 91%1 appear realistic in relation to a return to participation but overly optimistic in relation to return to pre-injury level of sport and performance. Our data cannot be extrapolated to elite settings, where high return rates have been reported 3.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Hence, in light of our findings, previously reported RTS rates of 91%1 appear realistic in relation to a return to participation but overly optimistic in relation to return to pre-injury level of sport and performance. Our data cannot be extrapolated to elite settings, where high return rates have been reported 3.…”
supporting
confidence: 52%
“…A 2018 meta-analysis reports an overall return to sports (RTS) rate of 91% and high patient satisfaction following hip arthroscopy for femoroacetabular impingement syndrome (‘arthroscopy’ in this paper) 1. Even though three in four athletes were reported to return to pre-injury levels of sports, it remains unknown if they also reach their pre-injury level of performance.…”
mentioning
confidence: 84%
“…1 A recent metaanalysis reported an overall return-to-sport rate after hip arthroscopy of 75% at the same level or a higher level of competition. 2 Some series have shown a trend toward a higher rate of return in professional athletes compared with recreational athletes. 3,4 Two series have shown no significant difference in the rates of return to sport between professional football, basketball, hockey, and baseball players, although both series showed that professional hockey players had a shorter postarthroscopy career.…”
Section: See Related Article On Page 2834mentioning
confidence: 99%
“…Despite this expectation, physical activity-related outcomes are only reported in approximately a quarter of studies investigating surgical intervention for FAIS [8], returning to sport or play being the predominant outcome assessed. A high level of return to sport/ return to play following hip arthroscopy (88-91%) has been reported in a number of systematic reviews [9][10][11][12][13][14][15][16] ; however, recent study findings suggest the need for a more expansive analysis, beyond these simplified nominal criteria, to assess the wider impact of hip arthroscopy on physical activity. When adding the further consideration of level to sports status, Ishøi et al [17] identified a relatively low return to pre-injury sport at pre-injury level of 57%, and Thorborg et al [18] identified that at 1 year post-arthroscopy, only 25% of patients that met physical activity reference scores commensurate with those expected in a healthy population.…”
Section: Introductionmentioning
confidence: 99%